The Implementation of Examples Non Examples Learning Model With Mind Mapping to Improve Biology Learning Outcomes of High School Students - Sonalita Luciana Qaulin; Suratno Suratno; Siti Murdyah (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
This research is a classroom action research that aims to improve student learning outcomes through the application of the Example non-Example Learning Model with the Mind Mapping Technique. The subjects in this study were students of class XIC in the even semester of SMAU BPPT Darus Sholah in the 2018/2019 academic year with a total of 20 students. This research was conducted in two cycles. The stages of one cycle include: planning, acting, observing, and reflecting. The stages in the next cycle are revised planning, action, observation, and reflection. This is so for the next cycle until the expected increase is achieved. The results of the study indicate that student learning outcomes have improved both cognitive and affective aspects. In the cognitive aspect, the increase from pre-cycle to cycle 1 was 15%. Cycle 1 to cycle 2 has increased by 25%, and in pre-cycle to cycle 2 has increased by 40%. Meanwhile, the increase in the affective aspect from cycle 1 to cycle 2 was 5.14%. Based on the results found, that the application of the Example non Example learning model with the Mind Mapping technique can improve student learning outcomes in Class XIC SMAU BPPT Darus Sholah Jember.